TINDAK TUTUR DALAM PERSPEKTIF KAJIAN WACANA - Suyitno, Imam (Diksi, 2006)
All members of a society master at least one language and use it ininteraction and communication by which they are able to conduct social functionsto express their nature as social beings. As social activities, the interaction andcommunication reflect cultural products expressed in conversational discourse.With regards to the speech act theory, the discourse always occurs in a speechsituation, in which a speech event occurs. Speech events consist of speech acts. Onthe basis of these paradigms, we can conclude that in nature discourse is a set ofspeech acts so that the speech act theory can be used as an approach to analyzingdiscourses.Keywords: speech acts, discourse, discourse analysisA.